Moderating Ethics Auditors Influence of Competence, Accountability On Audit Quality - Hajering Hajering; Muhammad Suun; Muslim Muslim (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
The purpose of this study is to determine the extent of competence, accountability influences audit quality and how auditor ethics can moderate the relationship between competence and audit quality and between accountability and audit quality. The population in this study amounted to 55 auditors consisting of 10 Public Accountant Firms (PAF) that are officially registered in Makassar City and the sampling using census sampling techniques by taking all samples that are in the population. This research was conducted using quantitative data collection methods using field research by collecting field data using a questionnaire method distributed directly to the Auditor of the Public Accountant Office (PAO) in the Makassar area. Data analysis uses the Partial Least Square (PLS) approach. The result showed that Auditor Competency and Accountability had a positive and significant effect on audit quality. Competence and accountability have a positive and significant effect on audit quality by moderating auditor ethics.